ANALISIS PERTUMBUHAN ASURANSI PERIODE 2017 - 2021 (STUDI KASUS PT ASURANSI ALLIANZ LIFE INDONESIA) - Melia Ayu Lestari, (2023)
The purpose of this final project is to determine the growth of PT Asuransi Allianz Life Indonesia's insurance using five indicators: Assets, Investments, Equity, Gross Premiums, and Profit (Loss) Before Tax. The writing method used is quantitative descriptive. The data used is secondary data sourced from Financial Reports and Annual Reports taken from the last five years, specifically 2017 - 2021. Data collection was done through documentation and literature review methods. The results of this writing indicate the overall growth of PT Asuransi Allianz Life Indonesia during the period 2017 - 2021. Assets are measured by calculating the sum of liabilities and equity. The growth of PT Allianz Life Indonesia's assets was able to achieve the expected target and launch a renewal agenda, which is a business strategy with five pillars. Investments are measured using the ROI formula, calculated by dividing profit by investment value. The growth of investments for PT Allianz Life Indonesia is achieved by maintaining business and service growth, such as digitalization, human resources, and distribution channels. Equity is measured by dividing post-tax profit by equity. The growth of PT Asuransi Allianz Life Indonesia's equity is supported by strong cooperation with various banking partners such as HSBC, OCBC, and BTPN. Gross Premiums are measured by summing up premium rates and the amount of coverage. The growth of PT Allianz Life Indonesia's gross premiums is observed by considering the Indonesian Composite Stock Price Index (IHSG) as the second-best stock movement indicator in Asia. Lastly, Profit (Loss) Before Tax is measured by summing up the profit before tax and income tax formulas. The growth of PT Allianz Life Indonesia's profit (loss) before tax is achieved by continuously increasing the net earnings of issuers in various sectors and improving macroeconomic indicators in Indonesia.